Impact of Traffic Load Randomness on Fatigue of Steel Bridges - Adam Wysokowski (The Baltic Journal of Road and Bridge Engineering)
The article considers the influence of the randomness of traffic load on the fatigue of elements of steel bridge structures. The phenomenon occurs specifically in the case of bridges characterized by significant width, with many traffic lanes and a high vehicle velocity, especially in the case of heavy goods vehicles. It has been shown that underestimation of operational durability, including fatigue durability, can be up to 23%. Operational loads increase due to the overlapping of traffic loads, which leads to the increased fatigue of elements of steel bridge structures. In an effort to assess this influence and its value, elements of the problem of the randomness of road traffic loads were compiled and described, and a simulative analysis of the operational strength of various lengths (spans) of the main girders of bridges was carried out. The analyses showed that for the structures with spans length of up to 10.0 m, the influence of passing vehicles could be skipped in calculations, especially in the case of weak traffic.